Estimating the level of disease risk and biosecurity on commercial poultry farms in New Zealand. Issue 5 (2nd September 2020) - Greening, SS; Mulqueen, K; Rawdon, TG; French, NP; Gates, MC
ABSTRACT: Aims: To collect baseline data on the contact risk pathways and biosecurity practices of commercial poultry farms in New Zealand, investigate the relationship between the farm-level disease contact risks and biosecurity practices, and identify important poultry health concerns of producers. Methods: A cross-sectional survey of all registered New Zealand commercial poultry operations was conducted in 2016 collecting information on farm demographics, biosecurity practices, and contact risk pathways. Survey responses were used to generate an unweighted subjective disease risk score based on eight risk criteria and a subjective biosecurity score based on the frequency with which producers reported implementing seven biosecurity measures. Producer opinions towards poultry health issues were also determined. Results: Responses to the survey response were obtained from 120/414 (29.0%) producers, including 57/157 (36.3%) broiler, 33/169 (19.5%) layer, 24/55 (44%) breeder, and 6/32 (19%) other poultry production types. Median disease risk scores differed between production types (p < 0.001) and were lowest for breeder enterprises. The greatest risk for layer and broiler enterprises was from the potential movement of employees between sheds, and for breeder enterprises was the on- and off-farm movement of goods and services. Median biosecurity scores also differed between production types (p < 0.001), and were highest for breeder and broiler enterprises. Across all sectors there was no statistical correlation between biosecurity scores and disease risk scores. Producers showed a high level of concern over effectively managing biosecurity measures. Conclusions: The uptake of biosecurity measures in the commercial poultry farms surveyed was highly variable, with some having very low scores despite significant potential disease contact risks. This may be related to the low prevalence or absence of many important infectious poultry diseases in New Zealand leading farmers to believe there is a limited need to maintain good biosecurity as well as farmer uncertainty around the efficacy of different biosecurity measures. Further research is needed to understand barriers towards biosecurity adoption including evaluating the cost-effectiveness of biosecurity interventions.